Making a mark an introduction to trademarks for small and nedium-sized enterprises - World Intellectual Property Organization (Geneva, Switzerland WIPO, 2017)
Introduction -- Trademarks: 1. What is a trademark? -- 2. What elements can you use as a trademark to distinguish your products from others? -- 3. What is the difference between a trademark and a brand? -- 4. What use trademarks? -- Types of Trademarks: 5. What are service marks? -- 6. What are collective marks? -- 7. What are certification marks? -- 8. What is the relationship between trademarks, collective marks and certification marks? -- Creating Trademarks: 9. Why is it important to have a strong trademark? -- 10. How can you increase the distinctiveness of a trademark? -- 11. What should be kept in mind when selecting or creating a trademark? -- Protecting Trademarks: 12. How can your business protect its trademark(s)? -- 13. What other legal instruments are available to protect your brand image or other aspects of your products? -- 14. Why should your business register its trademark(s)? -- 15. What rights does trademark registration provide? -- 16. Is the registration of the company/trade name of your business the same thing as trademark registration? -- 17. What are the main reasons for rejecting an application? -- 18. Can you get a trademark free of charge or buy it from someone who does not need the trademark anymore? -- 19. How can you find out if your proposed sign conflicts with a competitor's trademark? -- 20. What are the costs associated with trademark creation and protection? -- 21. Who is authorized to apply for trademark registration? -- 22. Do you need a trademark agent to file a trademark application? -- 23. How long does it take to register a trademark? -- 24. How do you apply for a trademark registration? -- 25. For how long is your registered trademark protected? -- 26. Can identical trademarks coexist? -- 27. Do you need to register all small modifications to your trademark? -- 28. What happens if you want to use your trademark for a different product? -- 29. How can you protect the shape of your product? -- Trademarks Abroad: 30. Is trademark registration in your home country valid internationally? -- 31. Should you consider protecting your trademark abroad? -- 32. When and how can you register a trademark of your business abroad? -- 33. What is transliteration of a trademark and what are the challenges? -- Using Trademarks: 34. What is meant by "use" of a trademark? What is its relevance for a trademark owner? -- 35. Can you register a trademark without having used it? -- 36. Can your business use the same trademark for different products? -- 37. How should you use your trademark? -- 38. Can you use a competitor's trademark in your advertising? -- 39. What is a domain name and what does it have to do with trademarks? -- 40. What should be kept in mind when using trademarks on the Internet? -- 41. What is the role of a trademark supervisor or coordinator? -- Commercializing Trademarks: 42. Can you license your trademark to other businesses? -- 43. What fee or royalty rate should you expect to receive for your trademark? -- 44. What is the difference between an exclusive and non-exclusive license? -- 45. Should you grant an exclusive or non-exclusive license for your trademark? -- 46. What does a franchising agreement have to do with trademarks? -- 47. Is there any restrictions on selling the trademark of your business to another business? -- 48. Can other business resell your trademarked products without authorization? -- Enforcing Trademarks: 49. Why is it important to detect infringements? -- 50. When does another trademarks infringe your rights? -- 51. What should your business do if its trademark is being used by others without authorization? -- 52. How can your business prevent the importation of counterfeit trademark goods? -- 53. What are your options for settling an infringement claim out of court? -- Annex--Useful Websites. "Esta es una de una serie de guías sobre Propiedad Intelectual para Empresas. Busca explicar por qué la gestión eficaz de marcas registradas es importante para su negocio. La gestión de marcas registradas debe ser una parte integral de la estrategia de marca de cualquier empresa, grande o pequeña. Con nuevos mercados en desarrollo e Internet, las empresas ahora tienen más oportunidades, y más lucrativas, que nunca para crear marcas comerciales valiosas y más modelos comerciales que aseguren la visibilidad de su empresa. Sin embargo, estas oportunidades también imponen una mayor demanda a las empresas para salvaguardar y aprovechar sus derechos de marca registrada y evitar violar los derechos de marca registrada de otros.... Esta guía está destinada a ayudar a varias partes interesadas de negocios, especialmente empresarios y propietarios/gerentes de pequeñas y medianas empresas (PYMES)"--Página 6.
Table of contents: Introduction -- Trademarks: 1. What is a trademark? -- 2. What elements can you use as a trademark to distinguish your products from others? -- 3. What is the difference between a trademark and a brand? -- 4. What use trademarks? -- Types of Trademarks: 5. What are service marks? -- 6. What are collective marks? -- 7. What are certification marks? -- 8. What is the relationship between trademarks, collective marks and certification marks? -- Creating Trademarks: 9. Why is it important to have a strong trademark? -- 10. How can you increase the distinctiveness of a trademark? -- 11. What should be kept in mind when selecting or creating a trademark? -- Protecting Trademarks: 12. How can your business protect its trademark(s)? -- 13. What other legal instruments are available to protect your brand image or other aspects of your products? -- 14. Why should your business register its trademark(s)? -- 15. What rights does trademark registration provide? -- 16. Is the registration of the company/trade name of your business the same thing as trademark registration? -- 17. What are the main reasons for rejecting an application? -- 18. Can you get a trademark free of charge or buy it from someone who does not need the trademark anymore? -- 19. How can you find out if your proposed sign conflicts with a competitor's trademark? -- 20. What are the costs associated with trademark creation and protection? -- 21. Who is authorized to apply for trademark registration? -- 22. Do you need a trademark agent to file a trademark application? -- 23. How long does it take to register a trademark? -- 24. How do you apply for a trademark registration? -- 25. For how long is your registered trademark protected? -- 26. Can identical trademarks coexist? -- 27. Do you need to register all small modifications to your trademark? -- 28. What happens if you want to use your trademark for a different product? -- 29. How can you protect the shape of your product? -- Trademarks Abroad: 30. Is trademark registration in your home country valid internationally? -- 31. Should you consider protecting your trademark abroad? -- 32. When and how can you register a trademark of your business abroad? -- 33. What is transliteration of a trademark and what are the challenges? -- Using Trademarks: 34. What is meant by "use" of a trademark? What is its relevance for a trademark owner? -- 35. Can you register a trademark without having used it? -- 36. Can your business use the same trademark for different products? -- 37. How should you use your trademark? -- 38. Can you use a competitor's trademark in your advertising? -- 39. What is a domain name and what does it have to do with trademarks? -- 40. What should be kept in mind when using trademarks on the Internet? -- 41. What is the role of a trademark supervisor or coordinator? -- Commercializing Trademarks: 42. Can you license your trademark to other businesses? -- 43. What fee or royalty rate should you expect to receive for your trademark? -- 44. What is the difference between an exclusive and non-exclusive license? -- 45. Should you grant an exclusive or non-exclusive license for your trademark? -- 46. What does a franchising agreement have to do with trademarks? -- 47. Is there any restrictions on selling the trademark of your business to another business? -- 48. Can other business resell your trademarked products without authorization? -- Enforcing Trademarks: 49. Why is it important to detect infringements? -- 50. When does another trademarks infringe your rights? -- 51. What should your business do if its trademark is being used by others without authorization? -- 52. How can your business prevent the importation of counterfeit trademark goods? -- 53. What are your options for settling an infringement claim out of court? -- Annex--Useful Websites.
Keywords: PROPIEDAD INTELECTUAL -- MARCAS REGISTRADAS